Implementasi pembelajaran muatan lokal bahasa Jawa kurikulum merdeka pada sekolah dasar di daerah pedesaan - Ryan, Achmad Supriyanto; Insani, Nur Hanifah (Universitas Mulawarman, 2025)
This study focused to evaluate the implementation of Javanese local content learning in the merdeka curriculum at SD 2 Blimbing Kidul. The findings of this study can be used as a reference in efforts to develop Javanese language learning at the elementary school level. This research applies a qualitative approach with a single case study design. Researcher subject was SD 2 Blimbing Kidul. Participatory observation, semi-structured interviews, and documentation collection were used as techniques in collecting data. In analyzing the data, the Miles and Huberman model was used, while the validity of the data was tested using triangulation of methods and sources. The results indicate that the implementation of Javanese language learning in the merdeka curriculum has not run optimally, both in terms of planning, implementation, and assessment. The lack of variety in learning methods and assessments has an impact on low student involvement and achievement of learning objectives. In the assessment aspect, the assessments applied tend to be summative only, so they are unable to accommodate students' potential and development. Another obstacle is the limited references for teachers and the lack of creativity in developing learning media, which causes students to feel bored in the Javanese language learning process.